2023
DOI: 10.1007/s11606-022-07928-0
|View full text |Cite
|
Sign up to set email alerts
|

New Frontiers in Diabetes Care: Quality Improvement Study of a Population Health Team in Rural Critical Access Hospitals

Abstract: BACKGROUND: Rural populations are older, have higher diabetes prevalence, and have less improvement in diabetes-related mortality rates compared to urban counterparts. Rural communities have limited access to diabetes education and social support services. OBJECTIVE: Determine if an innovative population health program that integrates medical and social care models improves clinical outcomes for patients with type 2 diabetes in a resource-constrained, frontier area. DESIGN/PARTICIPANTS: Quality improvement coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…With a diagnosis, these efforts can be done efficiently. Population health studies in hypertension and diabetes have demonstrated improvements in care, and patient identification is simplified when International Classification of Diseases (ICD) codes can be searched electronically [ 28 , 29 ]. Without a diagnosis, population health initiatives become less efficient if they must start with screening [ 30 , 31 ].…”
Section: A Way Forwardmentioning
confidence: 99%
“…With a diagnosis, these efforts can be done efficiently. Population health studies in hypertension and diabetes have demonstrated improvements in care, and patient identification is simplified when International Classification of Diseases (ICD) codes can be searched electronically [ 28 , 29 ]. Without a diagnosis, population health initiatives become less efficient if they must start with screening [ 30 , 31 ].…”
Section: A Way Forwardmentioning
confidence: 99%